2015
DOI: 10.1155/2016/5309484
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility Assessment of PLCL‐Sericin Copolymer Membranes Using Wharton’s Jelly Mesenchymal Stem Cells

Abstract: Stem cells based tissue engineering requires biocompatible materials, which allow the cells to adhere, expand, and differentiate in a large scale. An ideal biomaterial for clinical application should be free from mammalian products which cause immune reactivities and pathogen infections. We invented a novel biodegradable poly(L-lactic-co-ε-caprolactone)-sericin (PLCL-SC) copolymer membrane which was fabricated by electrospinning. Membranes with concentrations of 2.5 or 5% (w/v) SC exhibited qualified texture c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 65 publications
0
8
1
Order By: Relevance
“…The ability of electrospun membranes to support the growth of various cell lineages, including Schwann cells, embryonic stem cells, neural stem cells and mesenchymal stem cells, has been reported . Olfactory ensheathing cells (OECs) are considered as peripheral nerve progenitor cells which develop from a peripheral origin .…”
Section: Introductionmentioning
confidence: 99%
“…The ability of electrospun membranes to support the growth of various cell lineages, including Schwann cells, embryonic stem cells, neural stem cells and mesenchymal stem cells, has been reported . Olfactory ensheathing cells (OECs) are considered as peripheral nerve progenitor cells which develop from a peripheral origin .…”
Section: Introductionmentioning
confidence: 99%
“…These results suggest that PLC is a flexible substrate for multiple applications in regenerative medicine and tissue engineering. The viability of attached cells, an important factor, definitely indicates the cytotoxicity and biocompatibility of novel materials [20,22]. Previous studies showed a non-cytotoxicity of PCL scaffolds either in 2D or 3D forms by maintenance proliferation and functions of various cell types, such as porcine chondrocytes [19], rat hippocampus [23], human bone marrow mesenchymal stem cells [24], and mouse embryonic stem cells [1].…”
Section: Discussionmentioning
confidence: 99%
“…Focal adhesion kinase (FAK) and cyclin-A protein expression levels were used as markers for cell proliferation and attachment, respectively. The assays were performed as described by Inthanon et al (2016) [20]. Briefly, cells were fixed in 4% (v/v) formaldehyde for 30 min at room temperature and then washed three times (5 min/wash) with ice-cold washing buffer (0.05% (v/v) Tween 20 in 1X PBS), with gentle rocking.…”
Section: Cell Proliferation and Attachment Assays By Elisamentioning
confidence: 99%
“…proliferation and attachment, respectively. The assays were performed as described by Inthanon et al (2016) [11]. Briefly, cells were fixed in 4% (v/v) formaldehyde for 30 min at room temperature and then washed three times (5 min/wash) with ice-cold washing buffer (0.05% (v/v) Tween 20 in 1X PBS) with gentle rocking.…”
Section: Introductionmentioning
confidence: 99%